Conducting Surveys in Dental Education Research: Guidelines and Reminders. Issue 3 (16th March 2020) - Magnuson, Britta; Jain, Shruti; Roomian, Tamar; Pagni, Sarah; Tran, Duong T.; Finkelman, Matthew D.
Abstract: The use of surveys is popular in dental education research. However, designing and conducting a survey can have many pitfalls. This article aims to prepare a new researcher or one with little experience to undertake survey research. It covers points such as survey design (including question construction), pilot testing for validity and reliability, sampling strategy, methods to increase response rates, logistical considerations, and items to include when writing the manuscript. Careful consideration of a survey from beginning to end can help one design and conduct a successful study that meets its research aims and adds valuable evidence to the literature.